A biztosítási szerződések hatályba lépésének egyes kérdései - Pribula, László (Debreceni Jogi Műhely, 2007)
The dispensation of justice most often makes decisions in legal disputes about contract law on the basis of the general rules of contract law. The freedom of making contracts and the dynamism of contract law have resulted in an agreement that the conditions of the contract and the general rules should generally be considered to an increasing extent rather than the special regulations referring to the given contract. However, there are some contracts which theme, subjects and content require the application of special rules that result in solutions hard to interpret for parties inexperienced in law and that are radically different from those recommended by the general rules of contract law. Insurance contracts are those type of contracts, where the rules determine when the contract comes into existence and effect and when the services are due. These regulations are based on a logic that is radically different from the general rules, so they can often lead to serious misunderstandings. It is discernable in the judiciary practice that the dispensation of justice respects the specific features of insurance contracts, but tries to interpret the rules in a way that draws near to the general rules of contract law. The decisions of the Hungarian Supreme Court give priority to the interests of the insured parties and allow in fewer cases when the insurance company is exempted of its obligation of payment. However, judiciary practice has little effect on the content of insurance law. It seems justified to make insurance companies work out as detailed and clear conditions as possible and make them disclose the orders basically concerning their obligation of running risks.